1981
DOI: 10.1093/brain/104.4.753
|View full text |Cite
|
Sign up to set email alerts
|

Regional Cerebral Oxygen Supply and Utilization in Dementia: A Clinical and Physiological Study With Oxygen-15 and Positron Tomography a Clinical and Physiological Study With Oxygen - 15 and Positron Tomohraphy

Abstract: The cerebral blood flow, oxygen extraction and oxygen utilization has been measured regionally in 22 dements, and 14 aged normal volunteers. Ten demented patients were studied twice at a six-month interval from initial measurements. The use of a steady-state 15O technique and positron tomography for measuring regional cerebral blood flow, regional oxygen extraction fraction and mean cerebral oxygen utilization is discussed. The limitations of measurements are reviewed in the light of the present results and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
206
4
2

Year Published

1983
1983
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 675 publications
(230 citation statements)
references
References 0 publications
18
206
4
2
Order By: Relevance
“…Older adults with the ε4 allele who engaged in more physical activity had greater memory-related activation in posterior temporal and parietal regions than non ε4-carriers or those with lower physical activity. This result is particularly interesting as these areas are some of the first regions of cortex to show metabolic deficits in early AD [169][170][171] . This work shows interesting influences of both APOE genotype and physical activity on memory-related brain activation in cognitively intact but genetically at-risk older adults, but it is not clear if this increase is compensatory or protective against future cognitive decline.…”
Section: Risk Factors For Alzheimer's Disease: Apoementioning
confidence: 88%
“…Older adults with the ε4 allele who engaged in more physical activity had greater memory-related activation in posterior temporal and parietal regions than non ε4-carriers or those with lower physical activity. This result is particularly interesting as these areas are some of the first regions of cortex to show metabolic deficits in early AD [169][170][171] . This work shows interesting influences of both APOE genotype and physical activity on memory-related brain activation in cognitively intact but genetically at-risk older adults, but it is not clear if this increase is compensatory or protective against future cognitive decline.…”
Section: Risk Factors For Alzheimer's Disease: Apoementioning
confidence: 88%
“…Shefer (1973) computed an overall loss of 20% in the cerebral neurons in aged compared with young subjects. Scheibel et al (1975) showed a marked decrease in the dendritic spines, i.e., the synapses, of this type (Frackowiak et al, 1981) The CBF studies of Schieve and Wilson (1953) appear meritorious (a) in demonstrating a lack of significant difference in CBF and CMR02 in healthy people with mean ages of 29, 40, and 64 years, and (b) in first suggesting two types of de mentia on the basis of the reactivity of the brain's blood vessels to CO2, Where the cerebral circula tion and metabolism responded to inhaled CO2, a dementia due to disease of the brain's vessels was postulated; where they did not respond to the va sodilating effect of CO2, a primary degenerative dis ease of the brain was suggested. As Hoyer (1982a,b) has so well reviewed it, the most common and most important form of degenerative dementia is the Alzheimer type of presenile or senile de mentia; the secondary or vasogenic dementia is best understood as a multiinfarct process.…”
Section: Organization Of Behavior (Adaptation)-disturbed (Organiza Timentioning
confidence: 91%
“…PET studies show that metabolic impairments develop during the early stages of AD, most notably in posterior association (parietotemporal and lateral temporal) and prefrontal cortices. Mild hypometabolism in the parietal association cortex of presymptomatic mutation carriers at risk for familial AD has also been reported (22,31,36). These glucose use deficits in AD patients, which may reflect both local neuronal degeneration and/or synaptic dysfunction due to cholinergic deafferentation, do not recover over time.…”
Section: Reductions Of Cerebral Glucose Metabolism After Cholinergic mentioning
confidence: 97%
“…There is also extensive synaptic and neuronal loss in allo-and neocortex, along with a marked degeneration and loss of cholinergic neurons within the basal forebrain (BF), and reduced choline acetyl transferase (ChAT) in cortex and hippocampus (7,8,10,14,66,79). Another common finding in affected individuals is reduced glucose metabolism in cortical and hippocampal regions, detected by positron emission tomography (PET), notable as these are the primary projection targets of BF cholinergic efferents (19,22,23).…”
Section: Introductionmentioning
confidence: 99%